Extracorporeal shockwaves therapy for finger stenosing tenosynovitis: a systematic review and meta-analysis - Zhang, Liyue; Luo, Yuan; Chen, Li; Zhang, Xiong; Chen, Jinli (Frontiers in Physiology, 2026)
BackgroundStenosing tenosynovitis is a common chronic tendon disease that seriously affects daily life and working ability. However, its treatment is very challenging and requires more effective treatment methods. A large number of clinical studies have shown that extracorporeal shock wave therapy (ESWT) may relieve the symptoms of stenosing tenosynovitis, but there are no published reviews or meta-analyses specifically and comprehensively evaluating its efficacy for this disease. Therefore, through conducting a meta-analysis, this study systematically evaluated the therapeutic effect of ESWT on stenosing tenosynovitis, aiming to provide evidence-based medical evidence for clinical decision-making.MethodsA literature search was conducted in PubMed, Embase, Web of Science, Cochrane Library, Wanfang, CNKI, and VIP databases. Randomized controlled trials (RCTS) on shock wave therapy for stenosing tenosynovitis from database establishment to June 2025. The limited languages are Chinese and English. The search terms include: “Extracorporeal shockwave therapy,” shock wave therapy, “HIFU therapy, “De quervain stenosing tenosynovitis,” Trigger Digits, “finger Snapping”. The extracted inclusion indicators included the pain score VAS or NRS, the QDASH Disability questionnaire (Quick Disabilities of the Arm, Shoulder, and Hand questionnaire), and the cooney wrist joint function score. After extracting the data, meta-analysis was conducted through Review Manager5.3 software and Stata17.0 software.ResultsTwelve studies were included, all of which were randomized controlled studies. The results showed that the experimental group was significantly superior to the control group in terms of pain relief, with a total effect size of −1.32 (95% CI: −1.85, −0.79), which was highly statistically significant (Z = 4.89, P < 0.00001). The QDASH score of the shock wave group was superior to that of the control group, and there was no statistically significant difference (MD = −6.14, 95% CI [−14.00, 1.72], P = 0.13, I2 = 78%). The Cooney score showed that there was a significant difference between the shock wave group and the control group (MD = 13.84, 95% CI [5.04, 22.64], P = 0.002, I2 = 95%); The evaluation of clinical efficacy showed that there were significant differences between the shock wave group and the control group (RR = 5.44, 95% CI [2.99, 9.90], P < 0.00001, I2 = 49%).ConclusionThe results of this meta-analysis show that ESWT has a positive effect on symptom improvement in patients with stenosing tenosynovitis, but there is currently a lack of sufficient and high-quality systematic data to support it. In the future, more rigorous and well-designed clinical studies with adequate sample sizes are needed to comprehensively verify the safety and efficacy of ESWT in treating stenotic tenosynovitis.